2017
DOI: 10.3390/nu9090975
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Outcomes at 24 Months of Age in Toddlers Supplemented with Arachidonic Acid and Docosahexaenoic Acid: Results of a Double Blind Randomized, Controlled Trial

Abstract: Little is known about arachidonic acid (ARA) and docosahexaenoic acid (DHA) requirements in toddlers. A longitudinal, double blind, controlled trial in toddlers (n = 133) age 13.4 ± 0.9 months (mean ± standard deviation), randomized to receive a DHA (200 mg/day) and ARA (200 mg/day) supplement (supplement) or a corn oil supplement (control) until age 24 months determined effects on neurodevelopment. We found no effect of the supplement on the Bayley Scales of Infant and Toddler Development 3rd Edition (Bayley-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…The positive correlation seen between ARA and omega-3 fatty acids corresponds with observations made in other studies [42,43]. For example, Luxwolda et al have found a bell curve relationship between erythrocyte omega--3 fatty acid and ARA [42].…”
Section: Cognitive Functioningsupporting
confidence: 87%
See 1 more Smart Citation
“…The positive correlation seen between ARA and omega-3 fatty acids corresponds with observations made in other studies [42,43]. For example, Luxwolda et al have found a bell curve relationship between erythrocyte omega--3 fatty acid and ARA [42].…”
Section: Cognitive Functioningsupporting
confidence: 87%
“…It appears that the incorporation of omega--3 and omega--6 long chain polyunsaturated fatty acids into cell membrane is highly regulated and the balance between the two fatty acid families is critical for orderly structural organisation and function of cellular and subcellular membranes. At the same time, studies have found that ARA supplementation improves infant neurodevelopment including cognition and language development [43][44][45]. Further studies are required to better understand the role of ARA in normal growth and development.…”
Section: Cognitive Functioningmentioning
confidence: 99%
“…There were eight RCTs involving n = 2532 infants [ 29 , 30 , 31 , 59 , 60 , 61 , 71 , 72 , 73 , 74 , 86 , 87 , 88 , 89 , 90 ]. Only two trials included infants that were breastfed [ 74 , 90 ] and the majority included only term-born infants [ 29 , 30 , 31 , 59 , 60 , 71 , 72 , 73 , 74 , 86 , 87 , 88 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only two trials included infants that were breastfed [ 74 , 90 ] and the majority included only term-born infants [ 29 , 30 , 31 , 59 , 60 , 71 , 72 , 73 , 74 , 86 , 87 , 88 , 90 ]. One RCT provided fish oil or olive oil capsules that were added to formula or breastmilk [ 74 ], one provided sprinkles to add to food [ 90 ], and six RCTs compared infant formula supplemented with DHA to infant formula devoid of DHA [ 29 , 30 , 31 , 59 , 60 , 61 , 71 , 72 , 73 , 86 , 87 , 88 ]. Infants received doses of DHA ranging from 0.12 to 0.96% of total fatty acids present in formula [ 29 , 30 , 31 , 59 , 60 , 61 , 71 , 72 , 73 , 86 , 87 , 88 ], or 250 to 280 mg DHA as oil per day [ 74 ], or up to 200 mg/d through sprinkles [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…DHA is considered essential for the cortical circuit maturation in the developing brain, and ARA is also critical for childhood growth, brain development and health [26]. In this matter, infants who received a supplement containing ARA (200 mg/day) and DHA (200 mg/day) from 12-24 months of age showed better cognition and language skills compared to those without supplementation [27]. An interesting issue is that the EF tested in the COGNIS study was supplemented with ARA (0.45%) and DHA (0.32%), while the SF only contained linoleic and α-linolenic acids.…”
Section: Discussionmentioning
confidence: 99%